Issues in Physics Practicals in an Open and Distance Learning Environment - P. Rajesh, Kumar; Thirumeni Subramaniam,; Mukherjee, T. K (The Asian Society of Open and Distance Education, 2005)
This paper reviews the objectives of physics practicals in physics education in relation to the hilosophy of open and distance learning programme. The various issues that arise in the implementation of physics experiment based on an existing practical model are presented. Two major concerns are the effectiveness of the practical sessions and sustaining the fundamentals of the open and distance learning programme. A new practical physics model is then proposed, which enables students to experience physics experiments without violating the open and distance learning programme fundamentals. (Authors' abstract)